Near-IR Fluorescent Tracer for Glucose-Uptake Monitoring in Live Cells - Jo, Ala; Sung, June; Lee, Sanghee; Nam, Hyunsung; Lee, Hyo Won; Park, Jongmin; Kim, Hwan Myung; Kim, Eunha; Park, Seung Bum (Bioconjugate Chemistry, 2018)
Fluorescent tracers for glucose-uptake monitoring could be used as chemical tools for diagnosis and for discovery of novel therapeutic agents via the development of phenotypic screening systems. Here we present a new near-infrared fluorescent glucose tracer, Glc-SiR-CO2H, for monitoring the cellular glucose uptake. By conjugating glucosamine with two different silicon rhodamine fluorochromes, we found that the net charge of fluorochromes has considerable effects on cellular uptake of the probe. Competition assay with d/l-glucose as well as Western blot analysis implied GLUT-dependent uptake mechanism of this probe. Finally, Glc-SiR-CO2H not only differentiates cancer cells from normal cells, but also allows monitoring anticancer effects in live cells.
Keywords: Chemical tools; Fluorescent tracers; Fluorochromes; Glucose uptake; Live cell; Near-infrared fluorescent; Near-IR; Phenotypic screening; Screening system; Therapeutic agents; Biological Transport; Cell Line; Cell Line, Tumor; Fluorescent Dyes; Glucosamine; Glucose; Glucose Transporter Type 1; Glucose Transporter Type 4; Humans; Mitochondria; Rhodamines; Silicon; Spectroscopy, Near-Infrared